Oral controlled-release oxycodone for uterine cramping pain after cesarean section - Liu, Qin; Zhao, Jin-ning; Chen, Hui-xiang; Zhong, Tai-di (Zhong hua yi xue za zhi, 2011)
To evaluate whether combined oral oxycodone hydrochloride controlled-release tablets plus paracetamol and tramadol hydrochloride tablets is better than epidural analgesia with respect to uterine cramping pain control and side effects after cesarean section. Sixty consecutive patients scheduled for cesarean section from April to May, 2010 were randomized to either patient-controlled epidural analgesia with 0.1% ropivacaine, 0.1 µg/ml sufentanil (for postoperative 48 h) plus injected pethidine on demand (EDA group) or controlled-release oxycodone (2 × 15 mg for 1st postoperative 24 h; 2 × 10 mg for 2nd postoperative 24 h), paracetamol & tramadol hydrochloride tablets (8 × 1 tablet for postoperative 48 h) orally plus pethidine injection on demand (OXY group). Two groups were compared with respects to uterine cramping pain control when the oxytocin infusion (20 U plus 500 ml 5% glucose solution, iv. gtt within 2 h) once per day for postoperative 3 days as determined by the means of a visual analogue scale (VAS), pethidine consumption, side effects and costs. The EDA group experienced significant more pain than the OXY group when the oxytocin infusion was administered (mm) [50.0 (15.0, 72.5) vs 25.0 (0, 40.0), 60.0 (47.5, 72.5) vs 20.0 (0, 30.0), 35.0 (20.0, 50.0) vs 0 (0, 20.0)]. all P < 0.05). Pethidine was used for pain control in 2 patients (150 mg total) of EDA group during the oxytocin infusion whereas none of the OXY group received an injection of pethidine. There was a higher level of maternal satisfaction with a lower analgesic dose in the EDA group (80.9 ± 9.3 vs 90.0 ± 9.8, P < 0.01). The median duration of hospital stay was around 5 days in both groups. Postoperative pain control after cesarean section with the above combined regimen is superior to EDA in terms of a lower cost and a higher level of maternal satisfaction.